Hindu Teacher Religion Learning Strategy In SMA Negeri 5 Denpasar - Dharmaningsih, Ni Made Sri Uttami; Tanu, I Ketut; Sutriyanti, Ni Komang (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
Technological developments and information flows add to the tendency of high rates of deviation by students. The responsibility of the school to further enhance its role through the teacher in providing moral education so as to form students' self-efficacy in behaving appropriately and improperly. Students' understanding of values can be formed through the learning process. The role of teachers, especially teachers of Hinduism, in implementing learning strategies is the main focus to be studied. Thus, through this study will be known learning strategies carried out by Hinduism teachers in anticipating student behavior and foster self-efficacy and instill educational values that characterize in Denpasar Public High School 5. Based on the above background, problems can be formulated as follows: Application of the Hindu religion teacher learning strategy in improving moral behavior and self-efficacy in Denpasar 5 SMA 2) Factors that influence the implementation of the Hindu religion teacher learning strategies in improving moral behavior and self-efficacy at SMA Negeri 5 Denpasar 3) Implications of the application of the learning strategy of Hindu religious education on moral behavior and self-efficacy in Denpasar SMA 5. This problem will be studied using Learning Theory, Constructivism Theory, and Stimulus Response Theory. Data collection techniques used: observation, interviews, documents, literature studies with the determination of informants using purposive sampling technique. Data analysis used is qualitative descriptive and triangulation. The results of this study are presented as follows: (1) Application of the Hindu religion teacher learning strategy using scientific learning strategies which include: (a) Implementation and Evaluation Planning; (b) Learning methods, media and learning resources used. (2) Factors that influence the implementation of Hindu religion teacher learning strategies include internal factors and external factors. Internal factors consist of (a) Teacher Factors; (b) Student Factors; (c) School Management Factors; and (d) Learning Support Facilities and Infrastructure Factors. External factors consist of (a) social environment and (b) natural environment. (3) The implications of the implementation of learning strategies for Hindu religious education are (1) cognitive aspects, (2) affective aspects and (3) psychomotor aspects. Based on the description above, it can be concluded that the Hindu education learning strategy conducted at Denpasar Public High School 5 has its own method in its application, so it is able to control and overcome students from behavioral deviations and self-efficacy.